Nurses' perceptions, attitudes, and perspectives in relation to climate change and sustainable healthcare practices: A systematic review - Ebenezer Akore Yeboah; Amanda Rodrigues Amorim Adegboye; Rosie Kneafsey (Elsevier, 2024)
Background: Climate change threatens human existence and is caused by increasing carbon emissions. Healthcare systems generate about 5% of global net CO2 emissions, further contributing to the crisis. Green healthcare practices could be implemented and nurses, as the largest workforce group, could potentially drive these practices. This review explored nurses' awareness, perceptions, attitudes and perspectives towards sustainable nursing and healthcare practices concerning climate change. Methods: The Joanna Briggs Institute [JBI] methodology for conducting mixed methods systematic reviews was applied and results were reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses [PRISMA] guidelines. CINAHL, PsycINFO, SCOPUS, and PUBMED databases were searched. JBI and Mixed Method Appraisal Tool [MMAT] critical appraisal tools were used for the data appraisal. Data synthesis and integration followed the JBI convergent integrated approach and thematic analysis was performed. https://doi.org/10.17605/OSF.IO/8H3TC. Findings: Eighteen papers were included that represented nine different countries across five continents. One study was found in Africa, no studies in South America, and three in Asia. Five key themes were identified: i) knowledge and awareness of climate change, ii) link between nursing and climate change, iii) environmental sustainability, iv) barriers to environmentally responsible healthcare, and v) routes to environmentally sustainable nursing practices. Interpretation: The review indicates the need to raise awareness regarding climate change and sustainable practices among nurses. It is vital policy makers, and healthcare leaders ensure criteria relating to environmental sustainability and carbon reduction are included in decisions about procurement and service delivery. Nurses' engagement could drive forward a net-zero agenda.